Evaluation of the Effect of Trypsin Digestion Buffers on Artificial Deamidation - Hao, Piliang (2015)
Nonenzymatic deamidation occurs readily under the condition of trypsin digestion, resulting in the identification of many artificial deamidation sites. To evaluate the effect of trypsin digestion buffers on artificial deamidation, we compared the three commonly used buffers Tris-HCl (pH 8), ammonium bicarbonate (ABC), and triethylammonium bicarbonate (TEAB), and ammonium acetate (pH 6), which was reported to reduce Asn deamidation. iTRAQ quantification on rat kidney tissue digested in these four buffers indicates that artificial Asn deamidation is produced in the order of ammonium acetate < Tris-HCl < ABC < TEAB, and Gln deamidation has no significant differences in all tested buffers. Label-free experiments show the same trend, while protein and unique peptide identification are comparable using these four buffers. To explain the differences of these four buffers in producing artificial Asn deamidation, we determined the half-life of Asn deamidation in these buffers using synthetic peptides containing -Asn-Gly- sequences. It is 51.4 ± 6.0 days in 50 mM of ammonium acetate (pH 6) at 37 °C, which is about 23, 104, and 137 times that in Tris-HCl, ABC, and TEAB buffers, respectively. In conclusion, ammonium acetate (pH 6) is more suitable than other tested buffers for characterizing endogenous deamidation and N-glycosylation.